Nutri Edu Fun as Strategy to increase Knowledge of Health and Nutrition in the Community - Yusuf, Andi Mukramin; Alfiah, Elma; Puspa, Amalina Ratih; Prasetyawati, Annisa Dini; Orchidhea, Khalda Rahmah; Denaneer, Kyla; Rosyidi, Muhammad Naufal; Azzahra, Nabila Widya; Patricia, Wulandari (Universitas Padjadjaran, 2024)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition in the first 1000 days of life. The aim of implementing Nutri Edu Fun is to increase public awareness regarding the importance of a healthy and nutritious lifestyle, consuming halal food and thayyib to prevent stunting. Activities will be carried out on August - September 2023 in Cibening Village, Bekasi, West Java. The Nutri Edu Fun program consists of a village potential survey, Focus Group Discussion (FGD), collecting data on social mapping and household food security status, anthropometric measurements at posyandu, apart from that, additional activities are also carried out by PMT cooking competitions and demonstrations, follow-up FGDs at Cibening Village Office, and making the book